2012
DOI: 10.1007/s11207-012-0200-9
|View full text |Cite
|
Sign up to set email alerts
|

On-Orbit Sensitivity Evolution of the EUV Imaging Spectrometer on Hinode

Abstract: K in the quiet-Sun data exhibit solar-cycle effects.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 18 publications
5
17
1
Order By: Relevance
“…This is assumed in the remainder of the paper. We note that this result is in stark contrast to the conclusions reached by Kamio & Mariska (2012) and Mariska (2013). We will return to this point in the conclusions.…”
Section: Sw and Lw Line Radiancescontrasting
confidence: 56%
See 3 more Smart Citations
“…This is assumed in the remainder of the paper. We note that this result is in stark contrast to the conclusions reached by Kamio & Mariska (2012) and Mariska (2013). We will return to this point in the conclusions.…”
Section: Sw and Lw Line Radiancescontrasting
confidence: 56%
“…We use QS observations. There are no Si vii lines in the SW channel, but Kamio & Mariska (2012) and Mariska (2013) suggested the use of the Si vii 275.3 Å vs. Fe viii 185.2 Å ratio to monitor the relative sensitivity of the LW/SW channels. We will discuss this issue below.…”
Section: Silicon and Sulfur Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution of the EIS sensitivity has also been monitored through quiet-Sun observations. Mariska (2013) found that the intensities of various lines apparently decayed over time, with a time constant of about 20 years, suggesting a very stable calibration.…”
Section: Systematic Uncertaintiesmentioning
confidence: 94%